2013
DOI: 10.1177/1534484312469100
|View full text |Cite
|
Sign up to set email alerts
|

A Gendered Analysis of Emotional Intelligence in the Workplace

Abstract: Drawing on a sociological analysis considering gender, this article explores how emotional intelligence (EI) abilities are socially constructed and valued. It presents a range of societal trends including “the future is female” to explore how both men and women are perceived and judged against symbolic representations of masculine and feminine when they perform gendered conceptions of EI. The article illuminates how women and men may be encouraged to take up feminine and masculine interpretations of EI skills … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 84 publications
0
14
1
Order By: Relevance
“…Yet concluding that a feminine orientation gives higher EI will not hold good as the proportion of the gender role profiles was found to be uneven in the present study. However, the earlier research findings that expression of feminine traits contributes to higher emotional intelligence levels perhaps can explain the higher emotional intelligence scores of 'feminine' gender role identities (Thory, 2012). It was found that it was the men who were adopting feminine attributes in our study.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Yet concluding that a feminine orientation gives higher EI will not hold good as the proportion of the gender role profiles was found to be uneven in the present study. However, the earlier research findings that expression of feminine traits contributes to higher emotional intelligence levels perhaps can explain the higher emotional intelligence scores of 'feminine' gender role identities (Thory, 2012). It was found that it was the men who were adopting feminine attributes in our study.…”
Section: Discussioncontrasting
confidence: 65%
“…However, many of the empirical researches later concerned on gender differences in EI. With increased women in work force now and more to come (Elder & Johnson, 2001;Wirth, 2001; Rupavataram, 2017), a concept like emotional intelligence which is primarily concerned with expression and management of emotions, it was postulated that women are better in expression of emotions and hence will have better scoring on emotional intelligence (Garner & Estep, 2001;Gartzia et al, 2012;Thory, 2012). A biological explanation for this says that the cerebral processing of emotions differs between men and women, that women's biochemistry is better prepared to consider one's own emotions and those of others as certain part of the brain dedicated to emotional processing seems to be larger than men (Petridges & Furnham, 2000; Fernandez-Berrocal et al, 2012).…”
Section: Sex and Emotional Intelligencementioning
confidence: 99%
“…That said, this comes with its own risks of reducing focus to the development of high potential employees, in addition to reproducing value systems and potentially undermining the value of women and their type of emotional skills (Thory, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The research on stress especially related to comparison between gender has been mixed. In some studies, it has been observed that men experience more stress than women (Palmer et al, 2005;Thory, 2013;Mohan & Ashok, 2011;Tarafdar et al, 2011;Tandon et al, 2014). According to Swanson et al (1998) male medical doctors experience more occupational stress and less job satisfaction than female medical doctors (Swanson et al, 1998).…”
Section: Literature Reviewmentioning
confidence: 99%